2012
DOI: 10.1111/tpj.12002
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary force of AT‐rich repeats to trap genomic and episomal DNAs into the rice genome: lessons from endogenous pararetrovirus

Abstract: SUMMARYIn plant genomes, the incorporation of DNA segments is not a common method of artificial gene transfer. Nevertheless, various segments of pararetroviruses have been found in plant genomes in recent decades. The rice genome contains a number of segments of endogenous rice tungro bacilliform virus-like sequences (ERTBVs), many of which are present between AT dinucleotide repeats (ATrs). Comparison of genomic sequences between two closely related rice subspecies, japonica and indica, allowed us to verify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 63 publications
(102 reference statements)
1
34
0
Order By: Relevance
“…Each of the japonica, indica, and O. rufipogon genomes harbored about 100 copies of the eRTBVL-A, -B, -C, and -D families (this study, and Liu et al, 2012), but in different proportions. We examined the endogenization patterns of the eRTBVLs in each of the three genomes by comparing their relative abundances in the eRTBVL-A, -B, and -C families (Fig.…”
Section: Proportions Of Ertbvl Families In the Three Rice Genomesmentioning
confidence: 98%
See 2 more Smart Citations
“…Each of the japonica, indica, and O. rufipogon genomes harbored about 100 copies of the eRTBVL-A, -B, -C, and -D families (this study, and Liu et al, 2012), but in different proportions. We examined the endogenization patterns of the eRTBVLs in each of the three genomes by comparing their relative abundances in the eRTBVL-A, -B, and -C families (Fig.…”
Section: Proportions Of Ertbvl Families In the Three Rice Genomesmentioning
confidence: 98%
“…The disease is caused primarily by infection with rice tungro bacilliform virus (Caulimoviridae, Tungrovirus; RTBV), the known extant rice pararetrovirus (Hay et al, 1991;Qu et al, 1991). EPRV sequences, which share similarity with RTBV sequences, have been found in the genomes of cultivated rice, and these EPRV sequences have been referred to as endogenous RTBV-like (eRTBVL) sequences (Kunii et al, 2004;Liu et al, 2012). Intact virus genome sequences were assembled successfully from eRTBVL fragments collected from the Nipponbare genome database (Kunii et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Horizontal gene transfer across phylogenetic boundaries is another natural process that results in genetic variation in plants (Bock, 2010;Soucy et al, 2015), including transfer of DNA from bacteria, viruses, and unrelated plants (Bergthorsson et al, 2003;Staginnus et al, 2007;Liu et al, 2012;El Baidouri et al, 2014;Geering et al, 2014;Kyndt et al, 2015). One recent example was a study demonstrating that a wide selection of sweet potato [Ipomoea batatas (L.) Lam.…”
Section: Conventional Plant Breeding Sources Of Genetic Variation Usementioning
confidence: 99%
“…Nevertheless, a number of studies have revealed integrated sequences from members of most of the family Caulimoviridae genera, including badnaviruses, in plant genomes (Geering et al, 2001;Laney et al, 2012;Ndowora et al, 1999;Seal et al, 2014). These are known as endogenous pararetroviruses (EPRVs) (Geering et al, 2010) and probably arose from recombination between the viral and the host genome during repair of plant DNA breaks (Liu et al, 2012). The presence of an EPRV does not generally translate into an active (episomal) infection since such sequences are generally incomplete or rearranged and merely represent genetic fossils.…”
Section: Discussionmentioning
confidence: 98%